Forsythiasides: A review of the pharmacological effects - Yang, Hong-Xuan; Liu, Qiu-Ping; Zhou, Yan-Xi; Chen, Yu-Ying; An, Pei; Xing, Yi-Zhuo; Zhang, Lei; Jia, Min; Zhang, Hong (Frontiers in Cardiovascular Medicine, 2022)
Forsythiasides are a kind of phenylethanol glycosides existing in Forsythia suspensa (Thunb.) Vahl, which possesses extensive pharmacological activities. According to the different groups connected to the nucleus, forsythiasides can be divided into A-K. In recent years, numerous investigations have been carried out on forsythiasides A, B, C, D, E, and I, which have the effects of cardiovascular protection, anti-inflammation, anti-oxidation, neuroprotection, et al. Mechanistically, forsythiasides regulate toll-like receptor 4 (TLR4)/myeloid differentiation factor 88 (MyD88)/nuclear factor kappaB (NF-κB), nuclear factor-erythroid 2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) and other signaling pathways, as well as the expression of related cytokines and kinases. Further exploration and development may unearth more treatment potential of forsythiasides and provide more evidence for their clinical applications. In summary, forsythiasides have high development and application value.